Antioxidant Responses of Ragweed Leaf Beetle Ophraella communa (Coleoptera: Chrysomelidae) Exposed to Thermal Stress - Chen, Hongsong; Solangi, Ghulam Sarwar; Guo, Jianying; Wan, Fanghao; Zhou, Zhongshi (Frontiers in Physiology, 2018)
Ophraella communa LeSage is an effective biological control agent of common ragweed, Ambrosia artemisiifolia L., which competes with crops and causes allergic rhinitis and asthma. However, thermal stress negatively affects the developmental fitness and body size of this beetle. High temperatures cause a variety of physiological stress responses in insects, which can cause oxidative damage. We investigated the total protein content and activity of antioxidant enzyme including superoxide dismutase (SOD), catalase (CAT), peroxidases (POD) in O. communa adults when its different developmental stages were exposed to high temperatures (40, 42 and 44°C) for 3 h each day for 3, 5, 5, and 5 days, respectively (by stage), and a whole generation to high temperatures (40, 42, and 44°C) for 3 h each day. A control group was reared at 28 ± 2°C. Under short-term daily phasic high temperature stress, total protein contents were close to the control as a whole; overall, SOD activities increased significantly, CAT activities were closer to or even higher than the control, POD activities increased at 40°C, decreased at 42 or 44°C; stage-specific response was also observed. Under long-term daily phasic high temperature stress, total protein content increased significantly at 44°C, SOD activities increased at higher temperatures, decreased at 44°C; CAT activities of females increased at ≤ 42°C, decreased at 44°C, CAT activities of males decreased significantly; POD activities of females increased at 40°C, decreased at ≥ 42°C, POD activities of males decreased at 44°C; antioxidant enzyme activities in females were significantly higher than those in males. Antioxidative enzymes protect O. communa from oxidative damage caused by thermal stress.